The Politics of the Pantomime : Regional Identity in the Theatre 1860-1900. - Irwin, Harvey (University Of Hertfordshire Press, 2009)
Dynamic and unique, this history examines pantomime productions in the English provinces--especially Birmingham, Nottingham, and Manchester--from 1860 through 1900. Arguing that pantomimes were rooted in specific expressions of local identity, this volume explores censorship as well as the relationships between theaters, their managers, authors, and audiences. A valuable contribution to the study of Victorian popular culture, this account also demonstrates how regional pantomime theater utilized political satire to its full advantage due to its geographical and creative distance from London.